Evaluating Physical Indices for Determining Acute Malnutrition in Children: Evidence From Abuali Sina Balkhi Regional Hospital, 2023 - Qaderi, Mustafa; Mohsini, Mohammad Naser; Qarizada , Abdul Khaliq (Journal of Scientific Insights, 2025)
Childhood malnutrition remains a major public health challenge in developing countries. This study aimed to assess the prevalence of acute malnutrition and its associated factors among children aged over six months to five years who visited Abu Ali Sina Balkhi Regional Hospital in 2023. This descriptive-analytical study collected and analyzed data on weight, height, mid-upper arm circumference (MUAC), age, sex, and age group of the children. Inferential analysis using the Chi-square test indicated no statistically significant association between a child’s sex and the prevalence of malnutrition (p = 0.582). However, logistic regression analysis revealed that reductions in weight and height significantly increased the risk of malnutrition (p < 0.001), while chronological age and age grouping had no significant effect. Descriptive statistics further showed that although mean weight, height, and MUAC increased with age, they remained below global growth standards. The findings of this study highlight the importance of early identification of anthropometric indicators for timely diagnosis and intervention in malnutrition cases. Strengthening primary healthcare systems, improving family education, and implementing community-based nutritional therapy programs are key recommended strategies to reduce the prevalence of childhood malnutrition.